Transmission of force in the lumbosacral spine during backward falls - Van Toen, Carolyn; Sran, Meena M; Robinovitch, Stephen N; Cripton, Peter A (Spine (Philadelphia, Pa. 1976), 2012)
Mathematical model, combined with and verified using human subject data. (1) To develop and verify a lumped-parameter mathematical model for prediction of spine forces during backward falls; (2) to use this model to evaluate the effect of floor stiffness on spine forces during falls; and (3) to compare predicted impact forces with forces previously measured to fracture the spine. Vertebral fractures are the most common osteoporotic fractures and commonly result from falls from standing height. Compliant flooring reduces the force at the ground during a backward fall from standing; however, the effect on spine forces is unknown. A 6-df model of the body was developed and verified using data from 10 human subjects falling from standing onto 3 types of compliant floors (soft: 59 kN/m, medium: 67 kN/m, and firm: 95 kN/m). The simulated ground forces were compared with those measured experimentally. The model was also used to assess the effect of floor stiffness on spine forces at various intervertebral levels. There was less than 14% difference between model predictions and experimentally measured peak ground reaction forces, when averaged over all floor conditions. When compared with the rigid floor, average peak spine force attenuations of 46%, 43%, and 41% were achieved with the soft, medium, and firm floors, respectively (3.7, 3.9, 4.1 kN vs. 6.9 kN at L4/L5). Spine forces were lower than those at the ground and decreased cranially (4.9, 3.9, 3.7, 3.5 kN at the ground, L5/S1, L4/L5, and L3/L4, respectively, for the soft floor). Lowering the floor stiffness (from 400 to 59 kN/m) can attenuate peak lumbosacral spine forces in a backward fall onto the buttocks from standing by 46% (average peak from 6.9 to 3.7 kN at L4/L5) to values closer to the average tolerance of the spine to fracture (3.4 kN).